1977
DOI: 10.1128/iai.18.3.673-679.1977
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia and human leukocyte functions: effects on response of lymphocytes to mitogen and antigen and bactericidal capacity of monocytes and neutrophils

Abstract: It has recently been demonstrated that fever, or hyperthermia, results in enhanced survival of lizards infected by Aeromonas hydrophila. In the present study, the effects of hyperthermia on certain immune functions were assayed in vitro with purified human leukocytes. Lymphocyte transformation responses to the mitogen phytohemagglutinin and the common antigen streptokinase-streptodornase were enhanced at 38.5 degrees C relative to 37 degrees C whether analyzed according to absolute counts per minute of incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

1980
1980
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 48 publications
1
26
0
1
Order By: Relevance
“…Several studies implicated a relationship between inflammation and the production of HSPs (Karlsson et al, 1990;Cosgrove and Brown, 1983). Few studies, however, investigated how phagocyte functions such as RB activation are affected by heat stress (Roberts et al, 1977;Johansen et al, 1983). It has been suggested, though, that HSPs synthesized as a result of RB activation have a protective function that enables the macrophage to participate in protective immunity (Clerget and Polla, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies implicated a relationship between inflammation and the production of HSPs (Karlsson et al, 1990;Cosgrove and Brown, 1983). Few studies, however, investigated how phagocyte functions such as RB activation are affected by heat stress (Roberts et al, 1977;Johansen et al, 1983). It has been suggested, though, that HSPs synthesized as a result of RB activation have a protective function that enables the macrophage to participate in protective immunity (Clerget and Polla, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature effects on lymphocyte blastogenesis in vitro have been well documented [e.g., Roberts and Steigbigel, 1977;Smith et al, 1978;Ashman and Nahmias, 19781. The temperature sensitivity of lymphocyte blastogenesis makes it difficult, if not impossible, to interpret results of RF-exposure studies in vivo or in vitro if temperatures were not precisely and accurately controlled.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that T cell-mediated immunity began to work 5 days after infection with a sublethal dose of L. pneumophila in guinea pigs (15). Some studies indicated that hyperthermia was associated with enhancement of lymphocyte response to mitogen and antigen, by a commonly used assay for cell-mediated immunity (21,26). The febrile states observed in guinea pigs might promote the early development of a delayedtype skin reaction and blastoid transformation of spleen cells to L. pneumophila antigens.…”
Section: Effects Of Temperature On Intracellular Bacterial Killing Bymentioning
confidence: 99%